2023
DOI: 10.1039/d3bm00359k
|View full text |Cite
|
Sign up to set email alerts
|

Injectable chondroitin sulfate-grafted self-antioxidant hydrogels ameliorate nucleus pulposus degeneration against overactive inflammation

Abstract: Overactive inflammatory cascade accompanied with oxidative stress in nucleus pulposus exacerbates intervertebral disc degeneration (IVDD). Hydrogels have been demonstrated promising in treating IVDD, yet remains less efficacious in anti-inflammation supplemented...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 65 publications
0
4
0
Order By: Relevance
“…Inflammation is a complex biological process occurring in response to harmful stimuli causing injury to healthy tissue. Oxidative stress resulting from a high level of ROS is one of the key contributors to inflammation [ 92 93 ]. Therefore, balancing the ROS level via antioxidant supplementation is a promising strategy for treating inflammatory diseases.…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Inflammation is a complex biological process occurring in response to harmful stimuli causing injury to healthy tissue. Oxidative stress resulting from a high level of ROS is one of the key contributors to inflammation [ 92 93 ]. Therefore, balancing the ROS level via antioxidant supplementation is a promising strategy for treating inflammatory diseases.…”
Section: Reviewmentioning
confidence: 99%
“…Inflammation is a complex biological process occurring in response to harmful stimuli causing injury to healthy tissue. Oxidative stress resulting from a high level of ROS is one of the key contributors to inflammation [92,93] To increase the targeting ability, anti-inflammatory agents can be wrapped with a cell membrane camouflage technique [99][100][101]. For example, Ma et al constructed carbon dot-SOD nanozymes and CD98 CRISPR/Cas9 plasmids encapsulated in a metal-organic framework (MOF), and then camouflaged it with macrophage membrane [102].…”
Section: Inflammatory Diseasesmentioning
confidence: 99%
“…It demonstrated significant potential in regulating the balance of ECM metabolism within an abnormal microenvironment. Luo et al 101 demonstrated effective sustained delivery of chondroitin sulfate (CS). This hydrogel was found to successfully inhibit the expression of inflammatory cytokines and maintain a balance between anabolic and catabolic processes in an inflammation-simulated environment.…”
Section: Major Categories Of Ndds For Ivddmentioning
confidence: 99%
“… Chang et al 98 2022 Polymeric micelles Runx1 Rats In situ injection Increased hydration content, disc space height and ECM production. Chang et al 100 2022 Nanohydrogels circSTC2 Rats In situ injection Promoted ECM synthesis and repaired NP tissue Luo et al 101 2023 Nanohydrogels Chondroitin sulfate Rats In situ injection Anti-inflammation. …”
Section: Major Categories Of Ndds For Ivddmentioning
confidence: 99%